Concessões de serviços turísticos em áreas protegidas: uma análise da Cachoeira de Morangaba, Jundiaí/SP - Ribeiro, Sílvia Cristina Ignácio (2015)
Protected areas are vital components for the maintenance of natural areas and landscapes, conservation and preservation of biodiversity and the provision of opportunities for the development of local communities, ecotourism, environmental education and scientific research. However, these areas are in great challenges for most countries, especially in regard to its funding and management. In this perspective, this study shows the historical process of evolution of the issues related to the preservation and conservation in the world, and the historical, economic, social and legal conservation units in Brazil. In order to show some of the mechanisms and models of management systems for protected areas, the study provides an analysis on the concessions of tourist services and the types of possible partnerships between the public and private sectors, Non-Governmental Organizations and institutions. The case study of the waterfall Morangaba Jundiaí, SP, analyzes the public use that is permeated by different interests and meanings, its relationship with ecotourism and management systems available to the site. The survey results identified the potential and feasibility of of partnerships with NGO, educational institutions and private companies.